Safety and efficacy of l‐histidine monohydrochloride monohydrate produced by fermentation with Escherichia coli (NITE BP‐02526) for all animal species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Maryline Kouba; Mojca Kos Durjava; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2019)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l‐histidine monohydrochloride monohydrate produced by fermentation with Escherichia coli (NITE BP‐02526) when used as a nutritional additive or as a feed flavouring compound in feed and water for drinking for all animal species. The product under assessment is l‐histidine HCl H2O produced by fermentation with a genetically modified strain of E. coli (NITE BP‐02526). The production strain and its recombinant DNA were not detected in the final products. l‐Histidine HCl H2O does not give rise to any safety concern to the production strain. The use of l‐histidine HCl H2O is safe for the target species when used to supplement the diet in appropriate amounts. It is safe at the proposed use level of 25 mg/kg when used as a flavouring compound for all animal species. The use of l‐histidine HCl H2O in animal nutrition raises no safety concerns for consumers of animal products. The additive is not irritating to the skin or eyes and is not a skin sensitiser. There is a risk for persons handling the additive from the exposure to endotoxins by inhalation. The use of l‐histidine as a feed additive does not represent a risk to the environment. The additive l‐histidine HCl H2O is regarded as an effective source of the amino acid l‐histidine when used as a nutritional additive. For the supplemental l‐histidine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against degradation in the rumen. It is also considered efficacious as a feed flavouring compound under the proposed conditions of use.